(untitled) (Herald of Journalism, 2020)
In this article, the author talks about the development of scientific communication. The aim of the study was to identify the importance of scientific communication in the KazNU through the exchange of scien- tific information through databases RESEARCH-ID, THOMSON REUTERS, SCOPUS WEB OF SCIENCE, SPRINGER, benefits realization of the func- tions of scientific communication, communication transformation of the University in connection with the development of research scientists, as well as a reflection of basic forms of communication in the university par- ticipation in global projects of strategic importance (RIO + 20, G-Global).